Ambidexterity and Firm Productivity Performance: The Mediating Effect of Organizational Learning Capacity - Kitapçı, Hakan; Celik, Vural (Elsevier Science Bv, 2013)
Ambidexterity is emphasized as provides high firm performance. Additionally, so many researcher found that organizational learning capacity affects ambidexterity and firm performance. Lastly, it is emphasized that organizational learning capacity has highly relationship both ambidexterity and firm productivity performance. In this study, we aimed that a better understanding of that relationship by organizational learning capacity has a mediating effect on the relationship between ambidexterity and firm productivity performance. The survey of this study is conducted on 107 SME of 214 mid-level and high level managerial employees in metalworking industry in Turkey. The obtained data from the questionnaires are analyzed through SPSS. In consequence, we have reached that organizational learning capacity helps to explain the effect of ambidexterity on firm productivity performance.
9th International Strategic Management Conference -- JUN 27-29, 2013 -- Riga, LATVIA
Keywords: Ambidexterity; Organizatioanl Learning Capacity; Firm Productivty Performance